Hybrid molecules containing the B-domain of insulin-like growth factor I are recognized by carrier proteins of the growth factor. - De Vroede, M A (1985)
The insulin-like growth factors (IGFs) are polypeptides in plasma that are chemically related to insulin and have mitogenic and insulin-like activity. Unlike insulin, the IGFs circulate in plasma bound to specific high molecular weight carrier proteins that regulate their delivery to target tissues. To define the sites on the IGFs that allow them to be recognized by carrier proteins, we constructed hybrid molecules containing different portions of the insulin, IGF-I, and IGF-II molecules. The presence of the B domain of IGF-I, but not the D domain of IGF-II, enables these insulin-IGF hybrid molecules to be recognized by acid-stripped IGF carrier proteins from rat serum and other sources. By contrast, neither the BIGF-I nor DIGF-II domain is sufficient to enable binding to type II IGF receptors, despite the fact that type II receptors, like the carrier protein, specifically bind IGF-I and IGF-II but do not interact with insulin. By differentiating those sites on the IGF molecule required for binding to IGF carrier protein and receptors, the insulin-IGF hybrid molecules should help delineate the role of the carrier protein in presenting biologically active IGF to target tissues.